Pelatihan Siswa Jurusan Rekayasa Perangkat Lunak SMK Negeri 6 Kupang Dalam Rangka Kesiapan Ujian Kompetensi Keahlian (UKK) - Yohanes Payong; Eman Minggu; Yampi R. Kasesmetan (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Software engineering training is important for Vocational High School (SMK) students in facing the challenges of the Skills Competency Examination (UKK) in the industrial era 4.0. The literature review implies a gap between vocational school curricula and industry demands, emphasizing the need for additional training to prepare students with relevant practical skills. Previous research shows that collaboration with industry and the use of effective learning methods can improve the UKK results of vocational school students.  There is a significant increase in students' knowledge absorption capacity after attending the training. The t-test value of -18.375 with a significance of 0.000 shows that the difference in absorption capacity before and after training is very statistically significant. This means that the training provided has been effective in increasing students' understanding of database programming concepts. The training program that has been implemented has achieved its main objectives. Namely improving students' abilities in understanding and applying database programming concepts.